Chronic mild stress exacerbates severity of experimental autoimmune encephalomyelitis in association with altered non-coding RNA and metabolic biomarkers. (17th September 2017) - Gerrard, Brietta; Singh, Vaibhav; Babenko, Olena; Gauthier, Isabelle; Wee Yong, V.; Kovalchuk, Igor; Luczak, Artur; Metz, Gerlinde A.S.
Highlights: Exposure to stress exacerbated the clinical symptoms and allodynia in experimental autoimmune encephalomyelitis (EAE). Stress disrupted metabolic homeodynamics in EAE. EAE upregulated microRNA expression in spinal cord, which was exacerbated by stress. Stress alters epigenetic regulatory pathways and biomarkers related to MS. Abstract: The causal factors determining the onset and severity of multiple sclerosis (MS) are not well understood. Here, we investigated the influence of chronic stress on clinical symptoms, metabolic and epigenetic manifestations of experimental autoimmune encephalomyelitis (EAE), a common animal model of MS. Lewis rats were immunized for monophasic EAE with MBP69-88 and were exposed to chronic stress for 37 days starting 7 days prior to immunization. The exposure to stress accelerated and exacerbated the clinical symptoms of EAE. Both stress and EAE also disrupted metabolic status as indicated by trace elemental analysis in body hair. Stress particularly exacerbated chlorine deposition in EAE animals. Moreover, deep sequencing revealed a considerable impact of stress on microRNA expression in EAE. EAE by itself upregulated microRNA expression in lumbar spinal cord, including miR-21, miR-142-3p, miR-142-5p, miR-146a, and miR-155. Stress in EAE further up-regulated miR-16, miR-146a and miR-155 levels. The latter two microRNAs are recognized biomarkers of human MS. Thus, stress may synergistically exacerbate severity of EAE by altering epigenetic regulatory pathways. The findings suggest that stress may represent a significant risk factor for symptomatic deterioration in MS. Stress-related metabolic and microRNA signatures support their value as biomarkers for predicting the risk and severity of MS.